2016
DOI: 10.7883/yoken.jjid.2014.576
|View full text |Cite
|
Sign up to set email alerts
|

Biting Density and Distribution of <i>Aedes albopictus</i> during the September 2014 Outbreak of Dengue Fever in Yoyogi Park and the Vicinity of Tokyo Metropolis, Japan

Abstract: SUMMARY: A total of 160 autochthonous dengue cases transmitted by Aedes albopictus were reported between August and October of 2014 in Tokyo Metropolis, Japan. Ae. albopictus is a medically important vector of dengue virus, which has expanded its geographic distribution in temperate regions. Understanding the distribution and biting density of Ae. albopictus during the 2014 dengue outbreak in Tokyo is important to evaluate the epidemic risks of dengue fever in other highly populated cities in Europe and Asia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 21 publications
(20 reference statements)
1
49
0
Order By: Relevance
“…During the past 2 years (2014-2015) outbreaks of DF have also been reported in our neighboring countries such as China, 12 Japan, 18 Malaysia, 19 and Singapore. 19 This reminds us that we ought to pay more attention to this infectious disease as it is becoming an issue in southeastern Asian countries.…”
mentioning
confidence: 97%
“…During the past 2 years (2014-2015) outbreaks of DF have also been reported in our neighboring countries such as China, 12 Japan, 18 Malaysia, 19 and Singapore. 19 This reminds us that we ought to pay more attention to this infectious disease as it is becoming an issue in southeastern Asian countries.…”
mentioning
confidence: 97%
“…Tsuda et al [14] collected A. albopictus mosquitoes from Yoyogi Park on 4 and 5 September, 2014, and estimated that the overall mean density of biting mosquitoes was 7.13/person/8 min. A previous investigation of the arrival patterns of A. albopictus on a person during 30-min collection intervals showed that 56 and 68 % of the total female mosquitoes were collected during the first 5 and 10 min of the mosquito collection, respectively [15].…”
Section: Resultsmentioning
confidence: 99%
“…albopictus density and human biting within a city and across land-use types [21,39,56]. More field data and behavioral evaluation are needed to refine model assumptions and parameters regarding when and where mosquito density and percent human feeding is likely to facilitate onward human transmission.…”
Section: Discussionmentioning
confidence: 99%